Exploring the dimensions of urban quality of life associated with urban traffic jam: The development and validation of an instrument. (September 2022) - Nadrian, Haidar; Heizomi, Haleh; Shirzadi, Shayesteh; Moradi, Mohammad Sanyar; Hajibadali, Parisa
Abstract: Introduction: There is a gap in the literature on the domains of urban quality of life (UQOL) that are mostly affected by traffic and transport. Another gap is the lack of valid and reliable instruments to assess this concept and the domains associated with. In this paper, we report on the development of an instrument to measure urban QOL associated with urban traffic jam. Methods: Applying a mixed-method approach with sequential exploratory design, we developed the Urban QoL Questionnaire-associated with Traffic Jam (UQLQ-TJ) in two phases: at first, the experiences of 28 key informant residents on the aspects of their life quality associated with traffic jam were, qualitatively, explored. The answers to the research question in phase one provided us with specific items for use in putting into operation the UQLQ-TJ, which was, quantitatively, assessed in terms of validity and reliability, in a survey of 1042 residents. Findings: In phase one, the participants suggested seven dimensions of UQOL associated with traffic jam: family, physical, environmental, mobility, seniors, psychological, and socio-economic. The analysis of the survey, in phase two, appeared the validity and reliability of the seven dimensions. Confirmatory factor analysis showed goodness of fit (dif = 489, χ2 = 1665.372, χ2/df = 3.40, and P < 0.0001), and the indices RMSEA = 0.048, SRMR = 0.049, CFI = 0.909, and TLI = 0.900 confirmed that the model fit the data well. Conclusion: Our results supported the initial validity and reliability of the UQLQ-TJ, which may assist urban traffic and transport organizations in improving their interventional efforts. Application of UQLQ-TJ in such evaluations can provide the policymakers with a subjective estimation of multidisciplinary data that encompasses a wide range of urban planning features. The data retrieved using such a validated instrument may be particularly helpful in designing evidence-based health promotion interventions and urban lifestyle educational programs, focused on urban quality of life promotion and well-being. Highlights: There is a gap in the literature about the mostly affected domains of urban quality of life (UQOL) by traffic and transport. A mixed-method design was helpful in developing the Urban QoL Questionnaire-associated with Traffic Jam (UQLQ-TJ). Our results supported the initial validity and reliability of the UQLQ-TJ. Seven dimensions of UQLQ-TJ were family, physical, environmental, mobility, seniors, psychological, and socio-economic. The UQLQ-TJ represents a valuable self-report instrument for urban traffic and transport researchers and policy-makers.